Pemasaran Relasional di Koperasi Produsen Kopi (Studi Kasus di Koperasi Giri Senang, Kabupaten Bandung, Jawa Barat) - Senjaya, Devi Bellinda; Sadeli, Agriani Hermita (Universitas Galuh, 2024)
The rapid development of the business world requires business actors to keep up with progress in order to survive and compete in the marketplace. In order to survive and compete with other businesses, customer loyalty is essential. One of the ways to retain existing customers is to implement a marketing approach called relationship marketing. Relationship marketing serves as a strategy for companies to build long-term relationships not only with customers but also with other stakeholders, with the aim of increasing customer loyalty. This study aims to determine the patterns of relationship marketing and value network among stakeholders involved in Giri Senang Cooperative This research was conducted in Giri Senang Cooperative, located in Giri Mekar Village, Cilengkrang District, Bandung Regency. The data was collected through interviews with key informants involved in the business of the cooperative. This research design was descriptive qualitative and case study technique. This study shows that Giri Senang Cooperative has established good relationship with stakeholders even without contract system. The cooperative has implemented relationship marketing based on six market models including customer market, supplier and alliance market, influence market, referral market, recruitment market and internal market.